Ամերիկայի Միացյալ Նահանգների նախագահների ուղերձներն ու հայտարարությունները Հայոց ցեղասպանության տարելիցների կապակցությամբ (1976-2003 թթ.) - Արարատ Միրզոյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Прокламации президентов Соединенных Штатов Америки играют важную роль в процессе официального признания и осуждения Геноцида армян в США. Первый президент, заговоривший о Геноциде армян начиная с 1965г., когда этот процесс начался, был Джимми Картер. Начиная с него, президенты США, будучи еще кандидатами на пост президента, обещали в случае избрания признать геноцид, но после инаугураций забывали о своих обещаниях. Proclamations of the presidents of the United States of America play very important role in the process of the official acknowledgment and condemnation of the Armenian Genocide in the USA. The first president of the USA who spoke of the Armenian genocide since 1965, when the process started, was Jimmy Carter. Beginning from him, the presidents of the USA, being candidate for president, promised to acknowledge the genocide in case of being elected and forgot about their promises after the inaugurations.
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)